2019
DOI: 10.1590/0001-3765201920181235
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Anti-inflammatory and Antioxidant Properties of Safranal on CCI4-Induced Oxidative Stress and Inflammation in Rats

Abstract: The present study aimed to determine the antioxidative and anti-inflammatory effects of safranal on damage induced by CCl 4. Experimental animals were divided into five groups. The first group was determined as the control group and no treatment was conducted. Second group rats were administered 1 mL/kg-day CCI 4 during the experiment. Rats in Groups 3, 4 and 5 were administered 1 mL/kg-day CCI 4 and 25 mg/kg, 50 mg/kg; 100 mg/kg safranal, respectively via gavage. Oxidative-antioxidant parameters, liver functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 38 publications
1
13
0
1
Order By: Relevance
“…It was reported that safranal stabilized biomembranes in biological systems and reduced unsaturated membrane lipids and reactive oxygen species, effect of safranal on enhanced serum enzymes prevent infiltration of intracellular enzymes. (13) This is consistent with the commonly accepted view that, with the recovery of the hepatic parenchyma and hepatocyte regeneration, serum transaminase levels return to normal. (23) CP therapy lowers the amount of nuclear Nrf2 as well as NQO-1 and HO-1 (heme oxygenase-1) expression.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It was reported that safranal stabilized biomembranes in biological systems and reduced unsaturated membrane lipids and reactive oxygen species, effect of safranal on enhanced serum enzymes prevent infiltration of intracellular enzymes. (13) This is consistent with the commonly accepted view that, with the recovery of the hepatic parenchyma and hepatocyte regeneration, serum transaminase levels return to normal. (23) CP therapy lowers the amount of nuclear Nrf2 as well as NQO-1 and HO-1 (heme oxygenase-1) expression.…”
Section: Discussionsupporting
confidence: 91%
“…(29) Safranal has been reported to modulate the expression of antioxidant genes and regulate mitochondrial antioxidant genes, providing a lower radical potential for mitochondrial oxygen. (13) The increase in the cellular GSH content of, which may increase the GSH/GSSG ratio and decrease lipid peroxidation due to the effects of safranal. (30) The CP oxidative product responsible for the induction of LPO and the ROS under inflammation which will attack normal tissue and disrupt redox cycle, raising LPO (31) and significantly enhance the degree of lipid peroxidation in experimental animal livers with MDA as the most popular breakdown product.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CCl 4 was injected intraperitoneally on day 5 after starting propolis or distal water treatment. Other studies used similar doses of propolis and CCl 4 [26][27][28].…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…The kidney is an organ that is highly susceptible to damages that are caused by ROS may be because of the availability of long-chain poly-unsaturated fatty acids in formation of renal lipids (Ozbek, 2012), and tissue damage in the kidney may be due to the activity of pro-inflammatory cytokines like the TNF-α. Inflammation-stimulating cytokines may cause nephropathy through secretion from renal glomerular membrane (Alayunt et al, 2019).…”
Section: Effect Of Bht On Kidney Tissuementioning
confidence: 99%